Guide to Cloud Computing Principles and Practice - Hill, Richard; Hirsch, Laurie; Lake, Peter; Moshiri, Siavash; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Cloud computing platforms can allow organizations to become more efficient and more responsive to users of both internal and external systems, yet a clear understanding is needed in order to separate the facts from the hype behind this new and rapidly expanding area. This Guide to Cloud Computing describes the landscape of cloud computing from first principles, leading the reader step-by-step through the process of building and configuring a cloud environment. The book not only considers the technologies for designing and creating cloud computing platforms, but also the business models and frameworks in real-world implementation of cloud platforms. Emphasis is placed on (3z(Blearning by doing,(3y (Band readers are encouraged to experiment with a range of different tools and approaches. Topics and features: Includes review questions, hands-on exercises, study activities and discussion topics throughout the text Describes the key technologies involved in cloud computing Explores the use of cloud computing in business environments Demonstrates the approaches used to build cloud computing infrastructures Reviews the social, economic, and political aspects of the on-going growth in cloud computing use Discusses legal and security concerns in cloud computing Examines techniques for the appraisal of financial investment into cloud computing Identifies areas for further research within this rapidly-moving field This easy-to-follow and highly practical textbook/guide is an invaluable resource for advanced undergraduate and postgraduate students of software engineering, computer networking and related courses. The extensive worked examples will also appeal greatly to researchers, IT infrastructure technicians and application developers.s
Part I: Cloud Computing Fundamentals -- Introduction to Cloud Computing -- Business Adoption Models and Legal Aspects of the Cloud -- Social, Economic and Political Aspects of the Cloud -- Part II: Technological Context -- Cloud Technology -- Cloud Services -- Data in the Cloud -- Cloud and Web Intelligence -- Part III: Business Context -- Investment Appraisal -- Enterprise Cloud Computing -- Security and Governance -- Cloud Roadmap -- Challenges and the Future.
Keywords: Computer science; Computer network architectures; Data structures (Computer science).; Data encryption (Computer science).; Computer Science; Computer System Implementation; Information Systems Applications (incl. Internet).; Data Structures; Programming Techniques; Data Storage Representation; Data Encryption